Interior Museum Permainan Anak-Anak Tradisional Jawa di Surabaya - Halim, Florencia Melita (Intra, 2014)
Nowadays the Javanese traditional childrenâs games have started erased its existence. The development of technology, traditional games is now considered less interesting and have started being replaced with more modern toys and electronic toys. Whereas traditional game has many benefits for the development and growth of the child. With the presence of the museum of traditional childrens games are expected to introduce Java back knowledge about all kinds of Javanese traditional childrens games, as well as cultural values embodied in the traditional game. The design concept being used is the game gobak sodor. Gobak sodor is a group game and competition. While applications in materials, colors, furniture and interior, which are extracted from human motion playing gobak sodor, and competition in the game that is the opposite of games as well as paying attention to the museums main target function is intended for children. Adoption of these applications can be seen from the use and incorporation of dynamic and static forms, warm colours, namely orange that gives the impression of a dynamic, cheerful and uplifting and cold colours green gave the impression, tranquility and natural shade, natural materials of wood, parquet, bamboo and artificial materials include carpeting, pipe, and glass. In addition, applying local Javanese culture through elements of interior Â batik motifs.